Controlled reduction of isocyanates to formamides using monomeric magnesium - Kumar, Rohit; Sharma, Vishal; Banerjee, Subhrashis; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2023)
This work describes a transition metal-free methodology involving an efficient and controlled reduction of isocyanates to only formamide derivatives using pinacolborane (HBpin) as the hydrogenating agent and a bis(phosphino)carbazole ligand stabilized magnesium methyl complex (1) as the catalyst. A large number of substrates undergo selective hydroboration and give exclusively N-boryl formamides.